Factors contributing knowledge sharing in higher learning institution - Mohd Alwi, Najwa Hayaati; Abu Bakar, Azreena; Abdul Hamid, Hanifah (2008)
This paper is to discuss the factors that might be the contributors to the knowledge sharing in a Higher Learning Institution of Malaysia.Currently a study is conducted at a higher learning institution to identify the factors that can enhance the practice of knowledge sharing among the staffs regardless academic staffs or non - academic staffs. The study will be carried out by using two major approaches that are questionnaire survey and case studies.Therefore, the final product of this study is to compose the factors that have been determined within the study and it will be conferred in this paper.